Остеопороз в практике невропатолога - Луцкий, И.С.; Луцкая, Е.И.; Цыцевич, Д.Ю.; Коломийченко, Е.Б. (Актуальні проблеми транспортної медицини, 2005)
Обстежено 21 хворого з остеопорозом хребта. Детально описані клінічна картина неврологічних проявів захворювання, дані денситометрії. По вираженості больових відчуттів і характеру перебігу хвороби хворі
розділені на дві групи, що визначало тактику лікування. Відмічено, що порушення функції нервової системи завжди супроводжує розвиток і перебіг остеопорозу і часто є першим проявом захворювання. 21 patients with an osteoporosis of a backbone have been examined. A clinical pattern of neurological manifestations of the pathology under study and sectional X-ray spine bone densitometry data have been specified. Depending on algesic sensations and the disease course the patients have been divided into two groups. Their belonging to one or another group determined further curative tactics. It has been established that the development and course of osteoporosis is always accompanied with the infringement of the nervous system function accompanies and rather often is the first manifestation of the disease.